Environmental technical management model for the formalization of small mining - Caravelí - Arequipa - Alvarado Quispe, Carlos Santos (2021)
The problem of the formalization of small-scale mining is analyzed: small mining and artisanal mining, especially to the application of technical-environmental management, in Caravelí - Arequipa, identifying that the problem lies in the use and slowness, reaching a proposal of improvement of the processes of formalization of the (mining) activity, checking the process and its effectiveness, appreciating the problem and proposing an improvement in the normative and operational, which considers incentives, improvements, technification and efficient environmental management, for this the situation of the mining in Caravelí - Arequipa in order to optimize the management in the formalization of its (mining) activities. It was observed that this formalization has been carried out for years and has not had favorable advances, so the analysis was necessary and allowed to identify the main problems proposing a more effective and efficient management, fulfilling the purpose of the investigation, these arrangements that are the greatest Difficulties refers to: authorization of use of the surface land and ownership, exploitation contract y/o cession on the mining concession. The research has fulfilled everything necessary to be able to appreciate the study clearly to verify the result to be obtained.